Community pharmacists’ perception of knowledge, attitudes, and practices toward oral health promotion: A Cross-sectional study on the influence of training, demographics, and resources in the UAE - Khalid Awad Al-Kubaisi; Derar H. Abdel-Qader; Nadia Al Mazrouei; Ahmad Al-Azayzih; Semira Abdi Beshir; Asim Ahmed Elnour (PLoS ONE, 2025)
Community pharmacists (CPs) are crucial in promoting public health, including oral health, due to their accessibility and frequent patient interaction. This cross-sectional study examined factors influencing oral health promotion among 350 CPs in the UAE, focusing on training, demographic factors, and resource availability. Bivariate analysis showed that gender, years of experience, and the availability of a consultation area significantly influenced CPs’ confidence in providing oral health advice. Male pharmacists exhibited higher confidence in addressing tobacco-related dental issues compared to females. Those with a consultation area were more likely to perceive oral health promotion as part of their role. Multivariate logistic regression revealed that training significantly predicted engagement in oral health promotion. CPs who received formal training were seven times more likely to promote oral health (OR = 7.260, p < 0.001), while self-training had an even more substantial influence (OR = 39.249, p < 0.01). However, pharmacists who lacked sufficient workflow, staffing, and time were 87% less likely to perceive oral health promotion as part of their role (OR = 0.133, p < 0.001). The proximity of a dental clinic did not significantly affect pharmacists’ involvement in oral health promotion. In conclusion, this study emphasizes the importance of targeted training and adequate resources in encouraging CPs’ participation in oral health promotion. Pharmacists with more experience and access to training are more likely to take on proactive roles in promoting oral health.